PENINGKATAN KOMPETENSI GURU SD NEGERI 123/II TEBAT PELEPAT DALAM IMPLEMENTASI KURIKULUM MERDEKA - Tri Wiyoko; Dedek Helida Pitra; Fino Risqi Aryana (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2024)
This service activity was carried out to improve the competency of teachers at SD Negeri 123/II Tebat Pelepat in implementing the Independent Curriculum. This needs to be done because of the lack of facilities available to teachers at the school to study in more depth related to the Merdeka curriculum. Activities were carried out by providing practical workshops using lecture techniques, simulations, and discussions at the Pelepat VII Regional Coordinator office. The results of this activity had a good impact on teachers at SD Negeri 123/II Tebat Pelepat. Teachers who participated in the activity gained insight into knowledge related to the Pancasila student profile, the Discovery Learning learning model, and the Problem-Based Learning learning model. The knowledge teachers gain can increase teacher competency, influencing teacher readiness to carry out the learning process in the classroom. In this way, teachers are better prepared to carry out the learning process in the Merdeka curriculum.